Study guides

☆☆

Q: X4 plus 8x2 plus 4 - what are the factors?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

For any x ≠ 0, x2 -10/x2 - 4 +3x/x2 - 4 LCD = x2, multiply each term by their missing element of LCD = (x4 + 10 +3x - 8x2)/x = (x4 - 8x2 + 3x + 10)/x2

2x3 + 8x2 + 3x + 12 = (2x3 + 8x2) + (3x + 12) = 2x2(x + 4) + 3(x + 4) = (x + 4)(2x2 + 3) Since you have asked this question I am assuming that you are not yet at a level where you might want (2x2 + 3) factorised into its imaginary factors.

x4 +x2 =x2 (x2+1)

8x2 8x2

if 4 * 7 = x * 4, then x = (4 * 7) / 4 = 7

Related questions

For any x ≠ 0, x2 -10/x2 - 4 +3x/x2 - 4 LCD = x2, multiply each term by their missing element of LCD = (x4 + 10 +3x - 8x2)/x = (x4 - 8x2 + 3x + 10)/x2

It factors as (x2 -2x+2)(x2 +2x+2)

Answer this question…A. x4 + 2x3 + 9x2 + 4 B. x4 + 4x3 + 9x2 + 4 C. x4 + 2x3 + 9x2 + 4x + 4 D. x4 + 2x3 + 9x2 - 4x + 4

The question as stated is: x4 + 22 - 45 = x4 - 41 which has no rational factors. It is possible that the expression should have been x4 + 2x2 - 45 but that has no rational factors either.

4 x4 x4=64 + 13=77- - 4=81+(14x14=196)=277

2x3 + 8x2 + 3x + 12 = (2x3 + 8x2) + (3x + 12) = 2x2(x + 4) + 3(x + 4) = (x + 4)(2x2 + 3) Since you have asked this question I am assuming that you are not yet at a level where you might want (2x2 + 3) factorised into its imaginary factors.

(2x - 8)(-4x + 4) = -8x2 + 40x - 32

4-x4 = 0

(x + 4)(x + 3)(x + 1)

(x4 - 2x3 + 2x2 + x + 4) / (x2 + x + 1)You can work this out using long division:x2 - 3x + 4___________________________x2 + x + 1 ) x4 - 2x3 + 2x2 + x + 4x4 + x3 + x2-3x3 + x2 + x-3x3 - 3x2 - 3x4x2 + 4x + 44x2 + 4x + 40Râˆ´ x4 - 2x3 + 2x2 + x + 4 = (x2 + x + 1)(x2 - 3x + 4)

x4 +x2 =x2 (x2+1)

8x2 8x2

People also asked